Persepsi NU dan Muhammadiyah Mengenai Partisipasi Perempuan - ILHAM, LAMIA JOVITA ADITIA; DAMANIK, AHMAD TAUFAN (Politeia: Jurnal Ilmu Politik, 2017)
This study is about the perception of Nahdlatul Ulama (NU) and Muhammadiyah on womens participation. Muhammadiyah and Nahdlatul Ulama (NU)is the largest Islamic organization in Indonesia. Persyarikatan Muhammadiyah and Nahdlatul Ulama (NU) has been known since bebarapa twenty years ago.Muhammadiyah was established on 18 November 1912.Nahdlatul Ulama (NU) was established in Surabaya on January 31, 1926.Pioneers Muhammadiyah is K.H. Ahmad Dahlan and the founding pioneers Nahdlatul Ulama (NU) is KH. Hasyim Ashari. According to the scholars Nahdlatul Ulama role of women in politics is necessary to follow the current political participation. It would be better if Muslim women participated for the revival of Islam. According to the scholars Muhammadiyah women and men have a gender equality. Women needed to contribute ideas on political issues. The study used the approach to political ideology. This study method is descriptive. Collecting data with depth interview. Analysis of data using qualitative analysis. Keywords: Women in politics, political participation, Islamic perspective.